2024
DOI: 10.1038/s41467-024-45986-6
|View full text |Cite
|
Sign up to set email alerts
|

Tuning ferroelectric phase transition temperature by enantiomer fraction

Chang-Chun Fan,
Cheng-Dong Liu,
Bei-Dou Liang
et al.

Abstract: Tuning phase transition temperature is one of the central issues in phase transition materials. Herein, we report a case study of using enantiomer fraction engineering as a promising strategy to tune the Curie temperature (TC) and related properties of ferroelectrics. A series of metal-halide perovskite ferroelectrics (S−3AMP)x(R−3AMP)1−xPbBr4 was synthesized where 3AMP is the 3-(aminomethyl)piperidine divalent cation and enantiomer fraction x varies between 0 and 1 (0 and 1 = enantiomers; 0.5 = racemate). Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…As shown in Figure 2b, it can be observed that with the increase of x from 0.5 to 0.8, the main peak of the pre-sintered BaxSr1−xTiO3 powder shifts to the left at 31.6°. The variation in this phenomenon is attributed to the decrease in lattice parameters of the pre-sintered powder, which occurs as the Sr 2+ ion concentration increases, owing to the smaller ionic radius of Sr 2+ ions (1.44 Å) compared to Ba 2+ ions (1.61 Å) [23]. All lattice parameters are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2b, it can be observed that with the increase of x from 0.5 to 0.8, the main peak of the pre-sintered BaxSr1−xTiO3 powder shifts to the left at 31.6°. The variation in this phenomenon is attributed to the decrease in lattice parameters of the pre-sintered powder, which occurs as the Sr 2+ ion concentration increases, owing to the smaller ionic radius of Sr 2+ ions (1.44 Å) compared to Ba 2+ ions (1.61 Å) [23]. All lattice parameters are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, along with the increase in temperature, the dielectric loss significantly decreases further (≤0.005 at 100 • C). The decrease in dielectric loss with rising temperature can be attributed to the absence of domain walls in the paraelectric state[23]. The dielectric loss of the BST (0.8/0.2)-MLCC decreased at Tc, then it increased with temperature.…”
mentioning
confidence: 97%
“…6 The introduction of chirality usually brings optical rotation, 7 circular dichroism (CD), 8 and circularly polarized light (CPL) emission 4,9 in materials. In some cases, it can even induce non-centrosymmetry-related properties such as the bulk photovoltaic effect (BPVE), 10–12 second-harmonic generation, 13–15 piezoelectricity, 16,17 ferroelectricity, 18–20 Rashba splitting, 21,22 and topological quantum properties. 23 Although organic chiral materials exhibiting strong chiral activity in the near-ultraviolet region are widely available, the charge transfer capability of actual polarized optoelectronic devices is poor, 5 and there is an urgent need to develop new chiral lead iodide hybrids with strong absorption capacity and a broad light spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Also, an organic−inorganic hybrid cadmium-halide onedimensional perovskite has been reported to show a significant enhancement of piezoelectricity near the MPB, which is induced through solid-solution formation by mixing organic cations, 13 while changes in the crystal structure and ferroelectric transition temperature with compositional variation has recently been achieved in lead-halide two-dimensional perovskite ferroelectrics through enantiomeric organic cation mixing (i.e., racemization). 14 In this study, we report on the utility of a simple precipitation-based method to prepare solid solutions of the plastic/ferroelectric ionic crystal 1-azabicyclo[2.2.1]…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, solid solutions of ferroelectric PbTiO 3 with antiferroelectric PbZrO 3 (PZT) or relaxor Pb­(Mg 1/3 Nb 2/3 )­O 3 (PMN–PT) show a morphotropic phase boundary (MPB) in their composition–temperature phase diagrams. , A morphotropic transition is defined as an abrupt change in the crystal structure of the solid solutions with variation in composition, and electromechanical and dielectric responses of these ferroelectric solid solutions exhibit a significant enhancement in the vicinity of the MPB. Also, an organic–inorganic hybrid cadmium-halide one-dimensional perovskite has been reported to show a significant enhancement of piezoelectricity near the MPB, which is induced through solid-solution formation by mixing organic cations, while changes in the crystal structure and ferroelectric transition temperature with compositional variation has recently been achieved in lead-halide two-dimensional perovskite ferroelectrics through enantiomeric organic cation mixing (i.e., racemization) …”
Section: Introductionmentioning
confidence: 99%